Drug Intake and Actinic Keratosis: A Case-Control Study - Andrea Sechi; Ambra Di Altobrando; Eugenio Cerciello; Elisa Maietti; Annalisa Patrizi; Francesco Savoia (Mattioli1885, 2021)
Background: Actinic keratosis (AK) is a form of premalignant keratinocyte dysplasia. Recently, the role of photosensitizing drugs in the development of AK has been postulated. Objective: This study evaluated a possible association between the use of photosensitizing drugs and the development of AK.  A secondary aim was to identify a possible association between any medication other than those primarily examined and AK. Methods: A single-center, case-control study assessed the cumulative drug exposure of 90 patients with AK and 90 controls visiting a dermatology service for other skin ailments. Before the visit, patients were interviewed to collect data on daily therapy and the lag-time of discontinued drugs within the last 2 years, and to record the drug's active ingredient, dosage, and duration of therapy. In addition, sociodemographic characteristics including age, sex, educational level, skin phototype, and cumulative sun exposure habits were gathered. Results: By logistic regression, exposures to angiotensin II receptor blockers (ARBs) and antiplatelet agents were identified as independent risk factors for the development of AK. ARB intake was associated with AK only at high exposure (OR = 13.6; 95% CI, 2.0-93.8). The use of antiplatelet drugs was borderline, yet not significant, at low exposure (OR = 3.31; 95% CI, 0.86-12.7), but increased in a dose-dependent manner. The strongest correlation was found at the highest cumulative dose (>1100 dose unit-years (OR = 4.38; 95% CI, 1.16-16.6). Conclusions: High exposure to ARBs and antiplatelet agents may promote AK carcinogenesis in at-risk patients.